2022
DOI: 10.1111/evj.13878
|View full text |Cite
|
Sign up to set email alerts
|

Use of antimicrobials licensed for systemic administration in UK equine practice

Abstract: BackgroundJudicious antimicrobial use (AMU) is important for preserving therapeutic effectiveness. Large‐scale studies of antimicrobial prescribing can provide clinical benchmarks and help identify opportunities for improved stewardship.ObjectivesTo describe systemic AMU in UK equine practice and identify factors associated with systemic and Category B (third and fourth generation cephalosporins, quinolones and polymixins) AMU.Study designRetrospective cohort.MethodsAnonymised electronic patient records (EPRs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 36 publications
(84 reference statements)
3
11
1
Order By: Relevance
“…A recent study examining electronic patient records (EPRs) for all equids attended by five UK equine practices reported that HPCIA antimicrobials were prescribed in 8.2% of antimicrobial courses. 14 The most commonly reported indication in this study for use of 3rd or 4th generation cephalosporins was in foals. Neonatal sepsis has been most associated with gram negative infection, although the incidence of gram-positive infection is increasing.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…A recent study examining electronic patient records (EPRs) for all equids attended by five UK equine practices reported that HPCIA antimicrobials were prescribed in 8.2% of antimicrobial courses. 14 The most commonly reported indication in this study for use of 3rd or 4th generation cephalosporins was in foals. Neonatal sepsis has been most associated with gram negative infection, although the incidence of gram-positive infection is increasing.…”
Section: Discussionmentioning
confidence: 81%
“…18 More recent UK data using EPRs from equine practices in 2016-2017 showed that HPCIA antimicrobials were prescribed in 8.2% of courses and were used without prior C&S in 80.7% of courses. 14 This study highlights the frequent use of antimicrobials which are not currently authorised for use in the UK. In some clinical scenarios, these may be considered a first-line choice with consideration to antimicrobial susceptibility and responsible use, which highlights the importance of practice policies or treatment guidelines.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This retrospective study by Sarah Allen and UK‐based co‐workers aimed to describe systemic antimicrobial use (AMU) in UK equine practice and identify factors associated with systemic and Category B AMU .…”
Section: Antimicrobial Usementioning
confidence: 99%